Pengaruh Model Problem Based Learning Terhadap Hasil Belajar IPA Siswa Kelas VII SMP Ditinjau Dari Keterampilan Memecahkan Masalah - Septina Ratna Prabawa Shinta; Sigit Sujatmika (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2020)
The objective of this study was to determine the effect of the Problem Based Learning (PBL) model on science learning outcomes of class VII students of SMP in terms of problem solving skills. This research was a quasi-experimental research design, using pretest posttest. Descriptive results showed that the tendency of science learning outcomes with PBL models was obtained on average in the experimental class of 22.67 including very high categories, and classes taught by the lecture method were 17.47 in the high category. Whereas for problem solving skills students taught with PBL obtained an average of 78.54 which included high and class categories taught by the lecture method of 70.38 which included the high category as well. Based on the test of the Anakova obtained Fcount = 10.723 with p = 0.002. From the data obtained, the hypothesis was accepted and significant. Comparatively there were very significant differences in science learning outcomes of class VII students between PBL learning model and the expository model in terms of students' very significant problem solving skills.